1996
DOI: 10.1172/jci118687
|View full text |Cite
|
Sign up to set email alerts
|

Opposite regulation of human versus mouse apolipoprotein A-I by fibrates in human apolipoprotein A-I transgenic mice.

Abstract: The regulation of liver apolipoprotein (apo) A-I gene expression by fibrates was studied in human apo A-I transgenic mice containing a human genomic DNA fragment driving apo A-I expression in liver. Treatment with fenofibrate (0.5% wt/wt) for 7 d increased plasma human apo A-I levels up to 750% and HDL-cholesterol levels up to 200% with a shift to larger particles. The increase in human apo A-I plasma levels was time and dose dependent and was already evident after 3 d at the highest dose (0.5% wt/wt) of fenof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
158
2
3

Year Published

2006
2006
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 238 publications
(181 citation statements)
references
References 64 publications
15
158
2
3
Order By: Relevance
“…41 This study shows that the in vivo regulation of the human apoA-I gene in mice when it contains its proximal and distal regulatory sequences resembles the regulation of the mouse Apoa1 gene described previously. 20 The observed differences between the present and the previous studies, 20,23,24 can be explained based on the mechanism of transcriptional regulation of the human APOA-I gene that emerged from in vitro and in vivo studies. 25 In the transgenic mice used here, the expression of the human APOA-I gene was controlled by the proximal promoter and the distal APOCIII enhancer.…”
Section: Discussioncontrasting
confidence: 56%
See 4 more Smart Citations
“…41 This study shows that the in vivo regulation of the human apoA-I gene in mice when it contains its proximal and distal regulatory sequences resembles the regulation of the mouse Apoa1 gene described previously. 20 The observed differences between the present and the previous studies, 20,23,24 can be explained based on the mechanism of transcriptional regulation of the human APOA-I gene that emerged from in vitro and in vivo studies. 25 In the transgenic mice used here, the expression of the human APOA-I gene was controlled by the proximal promoter and the distal APOCIII enhancer.…”
Section: Discussioncontrasting
confidence: 56%
“…Two previous studies suggested that fenofibrate caused 2-to 2.6-fold increase in human APOA-I gene expression in ApoA-I transgenic mice, as well as a 3.5-to 7.5-fold increase in plasma ApoA-I levels. 20,23 These increases did not occur in ApoA-I transgenic mice in the PPARa-deficient background. 23 In ApoA-I transgenic rabbits, the higher doses of fenofibrate used increased hepatic human ApoA-I mRNA levels and plasma ApoA-I levels approximately 1.6-and 2-fold, respectively.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations